المباني الذكية بين حتمية التطبيق واشكالية التوافق - الغانم, نمير (Latakia University Journal -Engineering Sciences Series, 2018)
مع تزايد الاتجاه نحو اعتماد المعطيات الحديثة لتكنولوجيا البناء في العمارة متمثلة بما يسمى المباني الذكية بشكل مبالغ فيه حيناً ومقتضب تحكمه واقعية الحالة المعمارية المستهدفة حيناً آخر، يظهر التساؤل الذي يحاكم بين مدى حتمية تطبيق تلك المعطيات وجدواها على المدى البعيد؟ ومدى البعد التوافقي الواقعي لاعتمادها فعلياً والانطلاق نحو مستقبل معماري ذكي بمدخلاته ومخرجاته ؟ وعليه يهدف البحث لتسليط الضوء على المباني الذكية مفهوماً وتوجهاً للتوصل الى فهم نوعي لمدى ضرورة اعتمادها كتوجه مستقبلي لعمارتنا المحلية بشكل متكامل يمكن توجيهه وصياغته بما يتناسب وامكانية الحفاظ على مسافة أمان معماري يمكن عبرها ضمان ايجابية التغير باتجاه المستقبل. With the increasing trend towards the adoption of the modern data of building technology in architecture represented by the so-called smart buildings in an exaggerated and sometimes concise manner governed by the reality of the architectural state of the target, the question arises between the extent of the inevitability of the application of these data and their long-term feasibility? And the extent of the realistic consensus dimension for its actual adoption and the move towards a smart architectural future with its inputs and outputs? Therefore, the research aims to highlight the intelligent buildings concept and direction to reach a qualitative understanding of the need to adopt them as a future direction for our local economy in an integrated manner can be directed and formulated in proportion to the possibility of maintaining an architectural safety distance through which can ensure positive change in the direction of the future.